Experimental Study for a Micro Smart Grid to Meet the Energy Demand of a Household. (May 2017) - Ji, Jie; Zheng, Xiao; He, Cui; Zhang, Zhichao; Wang, Yaodong; Roskilly, Tony
Abstract: In this research, a smart grid using renewable energy and energy storage unit is studied. The system's storage units applies novel supercapacitor technologies to work with traditional batteries. This study aims at satisfying the dynamic demand of a household and evaluate the performance of the smart grid. The system design and the control strategy design is expressed in the paper combined with the discussion of the system's operation theory. The control panel of the system use SIEMENS S7-200 PLC as the core chipset. Digital software is an auxiliary tool for monitoring the system's operation process. The controlling method is divided into two situations, with renewable energy source and without renewable energy source, and both the operation processes are presented in detail in the results discussion part. After analysing the operation details of the system, the controlling strategy is proven to be useful for the operation of the smart grid system. Future work for the system is combining the electrical smart grid with other energy source. This system is potentially to be developed as electrical part of a multi energy system.